Child Abus: symptoms and repercussions in adulthood - BOURI , Nassima (Journal of Human Sciences, 2022)
The child who suffered psychological abuse of physical and mental abuse, or neglect, experienced behavioral problems of development and learning, mental health, physical and mental health in adolescence, general psychological deterioration, as well as an extreme lack of self-esteem and a degraded self-image of the person. Emotional abuse also leaves traces in adulthood. These abused children are often emotionally victimized during their adult lives, and may turn into irascible, hostile and aggressive adults.